Analisis Isi Pesan Syariah Pada Film Pantaskah Aku Berhijab Karya Hadrah Daeng Ratu - Sherlliana Sherlliana; Ahmad Sampurna (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to examine the sharia messages contained in the film "Pantaskah Aku Berhijab," directed by Hadrah Daeng Ratu. This study employed qualitative research, emphasizing the observation of dialogue, scenes, and visual symbols reflecting sharia values. The results indicate that the sharia messages in this film encompass three main aspects: sharia. The sharia aspect is manifested through the depiction of the obligation to wear the hijab as a form of obedience to Islamic teachings. The film also depicts the inner conflict and social pressures experienced by individuals in practicing sharia, thus providing a realistic depiction of the hijrah process. Thus, this film serves not only as entertainment but also as an effective da'wah medium in conveying Islamic values  to the community, especially the younger generation.